2020
DOI: 10.1186/s12888-020-02610-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the national multisite implementation of dialectical behaviour therapy in a community setting: a mixed methods approach

Abstract: Background: The implementation of evidence-based interventions for borderline personality disorder in community settings is important given that individuals with this diagnosis are often extensive users of both inpatient and outpatient mental health services. Although work in this area is limited, previous studies have identified facilitators and barriers to successful DBT implementation. This study seeks to expand on previous work by evaluating a coordinated implementation of DBT in community settings at a na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…A frequently reported barrier to implement the standard DBT program was the unwillingness of individual therapists to offer phone consultation. Flynn et al [ 60 ] reported similar findings in a survey exploring challenges experienced by clinical sites of implementation of DBT in community settings. Common issues concerned therapists’ reluctance, lack of management support and issues regarding clinical responsibility.…”
Section: Resultsmentioning
confidence: 68%
“…A frequently reported barrier to implement the standard DBT program was the unwillingness of individual therapists to offer phone consultation. Flynn et al [ 60 ] reported similar findings in a survey exploring challenges experienced by clinical sites of implementation of DBT in community settings. Common issues concerned therapists’ reluctance, lack of management support and issues regarding clinical responsibility.…”
Section: Resultsmentioning
confidence: 68%
“…Previous research suggests that the sectoral responsibility for IPS must be addressed more clearly as the service sits at the interface between public sectors responsible for welfare services and health services, which may confuse issues of ownership and responsibility [ 11 ]. Activities carried out prior to the start of the practical work, such as planning and fostering supportive organisational conditions, are especially important to the success of implementation, with a need for a mandatory service plan for coordinated implementation to be produced [ 56 , 57 ]. The importance of involving actors besides the employment specialists, such as clinical teams, in implementation is highlighted in the IPS international literature.…”
Section: Discussionmentioning
confidence: 99%
“…These features limit the extent to which comprehensive DBT can be implemented with fidelity in routine clinical settings, where limited funding and high staff turnover are common, and adherence to treatment models are not routinely monitored (Feigenbaum et al, 2012). The lack of organisational and administrative support, together with the limited funding and low prioritisation of introducing new, evidence-based practice in mental health, have all been cited as common barriers to implementation of DBT in public mental health at a global level (Carmel, Rose, & Fruzzetti, 2013; Flynn et al, 2020; King, Hibbs, Saville, & Swales, 2018; Swales et al, 2012).…”
Section: Introductionmentioning
confidence: 99%